Perancangan Alat Prediksi Cycle Time menggunakan Macro Excel dengan Metode Regresi Linear pada Produksi 1 Line 4 CV. Sinar Baja Electric - Jefferson Adrian Halim; I Gede Agus Widayana (Jurnal Titra, 2022)
In a manufacturing company, cycle time is the most crucial thing for a company. As a manufacturing company CV. Sinar Baja Electric does not have an accurate cycle time in every product, so there are some products that still do not have the suitable cycle time, which makes the productions become less effective and efficient. Therefore, an improvement is needed on the inaccurate cycle time. The improvement is intended for the company so that they can have a cycle time in every product that helps in every production process. Statistical test, statistical description analysis, standard time, hypothesis test and linear regression methods are used in this research. Later, data processing will be used for designing a cycle time prediction tool, using the macro excel with the visual basic application tool. Therefore the cycle time prediction tool can be used for predicting the cycle time in a product based on the processes.